Cross-beam energy transfer saturation: ion heating and pump depletion. (4th February 2022) - Hansen, A M; Nguyen, K L; Turnbull, D; Albright, B J; Follett, R K; Huff, R; Katz, J; Mastrosimone, D; Milder, A L; Yin, L; Palastro, J P; Froula, D H
Abstract: Cross-beam energy transfer (CBET) was measured in two regimes where the energy transfer saturation mechanism was determined by the plasma and laser beam conditions. Linear kinetic CBET theory agrees well with the measured energy transfer in all experimental configurations and at all probe beam intensities when accounting for pump depletion and the plasma conditions measured using Thomson-scattering. Simultaneous CBET and Thomson-scattering measurements enabled uncertainties in the plasma conditions to be isolated from CBET theory, which allowed the saturation mechanisms to be identified. In the perpendicular-beam configuration the saturation mode was through ion heating, which resulted from ion trapping in the driven waves and subsequent ion-ion collisional heating. In the co-propagating beam configuration there was minimal ion heating and the saturation mode was through pump depletion.